A Chartered Accountant's View of DCF Methods in Mineral Valuation (The Australasian Institute of Mining and Metallurgy, 1994)
DCF Valuations are very important to individuals and companies involved in the mining industry. Such valuations are critical to investment decisions in relation to new and existing projects. In particular they provide fundamental information to shareholders in the event of a capital raising or takeover and to financiers supporting mining companies and projects. Also, DCF Valuations are often used to support asset carrying values in the financial statements of mining companies. This paper presents a Chartered Accountant's (CA's) perspective on the main issues to be considered in preparing, analysing and relying upon DCF methods in mineral valuations and provides some practical examples relating to key issues. The paper makes the important point that DCF methods involve making assumptions about future events and circumstances that inherently contain uncertainty which results in a valuation prepared on a DCF basis providing a range of values that are not perfect or accurate. In order that DCF valuations provide meaningful information the underlying methodology used and assumptions made must be consistent, sound and well supported. Credibility of those involved in preparing mineral valuations is vital and this paper supports the adoption of sound practices by all concerned.